Keutamaan Bersuci Sebelum Melaksanakan Salat dalam Perspektif Hadis - Dzul Adli Muzhoffar Al Arifi (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about the virtue of purification. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about virtue in the history of Bukhari no. 132. The results and discussion of this study indicate that the status of hasan lighairihi quality hadiths that meet the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Bukhari no. 132 is relevant to be used as an illustration that one's prayer will not be accepted if it is not purified and the development of Islamic teachings about purification.